Fundamentals of HVAC control systems - McDowall, Robert
Heating, Ventilation and Air-Conditioning (HVAC)control systems are omnipresent in modern buildings. This book is an introduction to all those involved in the specification, design, manufacture, installation, operation or maintainance of these systems. The book explains: Control theory and how to evaluate, select, position and sequence the appropriate type of control. The electrical knowledge needed to understand controls and the use of electrical circuit drawings. The various types of valves and dampers, and their selection, installation and operation. Terminology and attributes of sensors, the selection of moisture sensors, pressure, flow, and auxiliary devices. Self-powered and system-powered controls. Electric controls, control diagrams and control logic. The components of pneumatic systems and control applications diagrams. Wiring conventions, application-specific electronic controllers and how to use them in HVAC applications. The use of written specifications, schedules, and drawings to clearly identify what is to be installed, how it is to be installed, and how it is expected to operate. Direct Digital Controls (DDC) components, their inputs and outputs, and the programming of DDC routines. DDC Networks and Protocols .DDC Specification, Installation and Commissioning After completing this course, you will understand: Control theory and how to evaluate, select, position and sequence the appropriate type of control. The electrical knowledge needed to understand controls and the use of electrical circuit drawings. The various types of valves and dampers, and their selection, installation and operation. Terminology and attributes of sensors, the selection of moisture sensors, pressure, flow, and auxiliary devices. Self-powered and system-powered controls. Electric controls, control diagrams and control logic. The components of pneumatic systems and control applications diagrams. Wiring conventions, application-specific electronic controllers and how to use them in HVAC applications. The use of written specifications, schedules, and drawings to clearly identify what is to be installed, how it is to be installed, and how it is expected to operate. Direct Digital Controls (DDC) components, their inputs and outputs, and the programming of DDC routines. DDC Networks and Protocols. DDC Specification, Installation and Commissioning.